Surgical treatment of oral submucosal fibrosis - Hifny, Sara Ahmed; AlShaikh, Lujain Khalil; Alharthi, Sana Ghazai; Abushanab, Renad Maher; Aldahian, Noha Abduallah; Alnamlah, Sarah Saleh; Aljohani, Sara Mohammed; Alghubairani, Haitham Amer; Almalik, Alghalia Essam; Neyaz, Raghad Yousef; Abdulaziz, Amro Mohammed (International Journal Of Community Medicine And Public Health, 2021)
Oral submucosal fibrosis is a serious condition that might be associated with serious complications in the affected patient. The disease also represents a major challenge to the healthcare specialists and the patient before achieving proper management of the condition. Different pharmacological and surgical interventions have been validated. However, no single modality has been proved as an adequate management approach for the disease, which is probably due to the limited number of investigations in this concern and the limited knowledge about the pathogenesis of the condition. In the present literature review, we have discussed the different surgical approaches that have been reported in the literature for managing patients with oral submucosal fibrosis. These approaches mainly aimed to remove the fibrous bands in the oral cavity and maintain adequate mouth opening. It should be noted that it would be hard to write a solid conclusion in this concern because most of the current evidence was either lacking or obtained from a limited number of studies with no proper sample sizes or adequate follow up durations. Accordingly, the indication of the surgical intervention should be primarily done by the surgeon based on the degree of involvement of the oral cavity. Finally, we recommended that further comparative investigations be carried out to further demonstrate the most appropriate management modality and to rule out whether pharmacological or surgical modalities are more efficacious in these settings.